"I Didn't Need People's Negative Thoughts": Women With Intellectual and Developmental Disabilities Reporting Attitudes Toward Their Pregnancy. Issue 3 (September 2019) - Potvin, Lynne A.; Barnett, Barbara M.; Brown, Hilary K.; Cobigo, Virginie
Background: Since the illegalization of involuntary sterilization of persons with intellectual and developmental disabilities, there has been an increase in childbearing in this population. However, women with intellectual and developmental disabilities continue to experience prejudicial attitudes toward their pregnancies. Objective: To analyze the experiences of women with intellectual and developmental disabilities regarding their perceptions of support persons' attitudes toward their pregnancies. Methods: Three case studies derived from grounded theory research exploring perinatal social support received by women with intellectual and developmental disabilities. Using inductive content analysis, we further analyzed the perceptions of women with intellectual and developmental disabilities regarding support persons' attitudes toward their pregnancies. Findings: The nature of interactions with support persons and women's characteristics, such as help-seeking behaviors, disability, mental illness, and age, influenced support persons' attitudes toward childbearing. Women preferred support from caregivers perceived as nonjudgmental and tended to restrict contact with persons perceived as prejudicial. However, some attitudes improved following positive interactions with the women. The relationship between support persons' attitudes and the women's help-seeking behaviors is thus complex. Conclusions: Education of families and medical and social services practitioners and opportunities for positive contact should be further explored. Caseworkers of women with intellectual and developmental disabilities may have invaluable roles in facilitating positive interactions between women with intellectual and developmental disabilities and caregivers.